Quy mô ngân hàng, tăng trưởng cho vay và rủi ro tín dụng: Bằng chứng thực nghiệm từ các ngân hàng thương mại ở Việt Nam - Le Hoang , Vinh; Phan Thi My , Duyen; Luong Dinh , Quang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The purpose of this paper is to confirm the non-linear impact of loan growth and bank size on credit risk at commercial banks in Vietnam. The sample covers 24 commercial banks from 2009 to 2019, the research data is collected from audited financial reports supplied by FiinGroup. The GLS estimation result shows that the credit risk is impacted by loan growth with U shape, and bank size with inverted-U shape. These relationships recommend that the commercial banks need to determine the threshold of loan growth and bank size, and it will serve as the foundation for setting up relevant policies to adjust credit risks in accordance with their goals. This paper will provide useful information for making decisions of credit risk managers and others.